The Amazing Wealth for Believers - “Christ in You, the Hope of Glory” - Thomas Sibley (Kairos (English Ed.))
The unique truth of the message which Paul proclaimed as “good news” was that God Himself would presently exist and live out his character, purpose, and care through those who received Christ Jesus as Lord. The church at Colossae had the privilege and responsibility to expose the “glory of God” in their corporate and private lives because of the miracle of the ongoing incarnation of Christ. This is still the “hope of Glory.”